Implikasi Krisis Energi Global dari Pembatasan Selat Hormuz terhadap Sengketa Ambalat dan Keamanan Asia Tenggara - Mutiara Azzahra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The global energy crisis resulting from disruptions in international energy supply chains has intensified states’ concerns regarding energy security and access to strategic natural resources. This study examines the implications of the global energy crisis triggered by restrictions in the Strait of Hormuz on the Ambalat Block dispute between Indonesia and Malaysia and its potential impact on regional security in Southeast Asia. Employing a qualitative research method with a library research approach, this study draws upon academic literature, government documents, international organization reports, and relevant policy publications. The analysis is conducted through the lens of realism, which emphasizes the role of states as rational actors pursuing national interests and security within a competitive international system. The findings indicate that the global energy crisis has increased the strategic significance of the Ambalat Block due to its substantial oil and gas reserves. Under these circumstances, Indonesia and Malaysia have sought to promote cooperation through a Joint Development Agreement (JDA) as a pragmatic mechanism to manage overlapping claims while enhancing energy security and maintaining bilateral stability. Nevertheless, the implementation of the JDA continues to face challenges, including legal uncertainty, jurisdictional ambiguities, environmental concerns, and domestic political pressures that may affect the sustainability of the arrangement. This study concludes that the global energy crisis extends beyond economic consequences and has the potential to reshape patterns of conflict and cooperation in strategically important maritime regions such as Ambalat.